Case series of pubic bone diastasis causing severe pelvic girdle pain in pregnancy - Gupta, Pooja; Malik, Renuka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Pelvic girdle pain (PGP) is a pregnancy discomfort that causes pain and limitation of mobility and functioning in any of the three pelvic joints. The patient usually presents antenatally with persistent suprapubic pain which is exaggerated during moving, walking or climbing stairs. Intrapartum, this could be associated with disruption of sacroiliac joint, hematuria and bladder dysfunction in severe cases. Pelvic X-rays, ultrasound, and magnetic resonance imaging aid in confirmation of diagnosis by measuring the degree of separation of symphysis. Treatment modalities range from conservative management to orthopedic interventions in form of pelvic strapping, open reduction and internal fixation. Postpartum pain often masks clinicians to make the diagnosis of pubic symphysis diastasis. A case series of three cases which were diagnosed and confirmed with ultrasound and managed with orthopedic consultation. till their delivery and in post-partum period till recovery. Although there is still no specific consensus on treatment guideline, management generally of conservative management to surgical in the form of pelvic bracing or strapping. Awareness of this rare condition can help in management of pain and associated disability which improves post-delivery.